PENGUJIAN PERATURAN DESA MENURUT UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Idea Islami Parasatya; Tin Yuliani (Media Keadilan: Jurnal Ilmu Hukum, 2019)
Law number 6 of 2014 concerning Villages recognizes the existence of villages and village autonomy, including adat villages as a legal community unit that has territorial boundaries. According to Law number 6 of 2014, village regulations determined by the Village Head after being discussed and agreed with the Village Consultative Body constitute the legal and policy framework in the administration of village governance and village development. The determination of village regulations is a translation of various authorities owned by the Village, referring to the provisions of the higher laws and regulations. As a legal product, village regulations must not conflict with higher regulations and must not harm the public interest. As a political product, village regulations processed democratically, and in a participatory manner, the drafting process involves the participation of village communities. Village communities have the right to propose or provide input to the Village Head and the Village Consultative Body in the process of drafting village regulations.Keywords: supervision of village regulations, village autonomy, village regulations ABSTRAKUndang-Undang nomor 6 tahun 2014 tentang Desa mengakui keberadaan desa dan otonomi desa termasuk desa adat sebagai kesatuan masyarakat hukum yang memiliki batas wilayah. Menurut Undang-Undang nomor 6 tahun 2014, peraturan desa ditetapkan oleh Kepala Desa setelah dibahas dan disepakati bersama Badan Permusyawaratan Desa merupakan kerangka hukum dan kebijakan dalam penyelenggaraan pemerintahan desa dan pembangunan desa. Penetapan peraturan desa merupakan penjabaran atas berbagai kewenangan yang dimilki Desa mengacu pada ketentuan peraturan perundang-undangan yang lebih tinggi. Sebagai sebuah produk hukum, peraturan desa tidak boleh bertentangan dengan peraturan yang lebih tinggi dan tidak boleh merugikan kepentingan umum. Sebagai sebuah produk politik, peraturan desa diproses secara demokratis dan partisipatif, yakni proses penyusunannya mengikutsertakan partisipasi masyarakat desa. Masyarakat desa mempunyai hak untuk mengusulkan atau memberikan masukan kepada Kepala Desa dan Badan Permusyawaratan Desa dalam proses penyusunan peraturan desa.Kata kunci: desa, peraturan desa, pengawasan peraturan desa, otonomi desa